Corrigendum to “A highly transparent and self-healing elastomer based on dynamically reversible heterocyclic interactions with enhanced toughness and outstanding rolling reliability” [Polymer Testing 147 (2025) 108803] - Choi, Kiwon; Jeon, Hyeryeon; Kim, Youngmin; Kim, Yongju; Hong, Pyong Hwa; Park, Jong Hyuk; Ko, Min Jae; Hong, Sung Woo (Elsevier BV, 2026)
The authors regret that the published version of the above article contained an error in the institutional affiliation of one of the co-authors, Dr. Jong Hyuk Park. This error arose entirely from the authors’ oversight during the final submission and proofreading stages. We sincerely acknowledge that the responsibility for ensuring the accuracy of author information lies solely with us, and we are grateful to the editorial office for the opportunity to address this mistake through this corrigendum. In the originally published article, Dr. Park's affiliation was incorrectly listed as: (b) Green Circulation R&D Department, Korea Institute of Industrial Technology, 89 Yangdaegiro-gil, Ipjang-myeon, Seobuk-gu, Cheonan-si, Chungcheongnam-do 31056, Republic of Korea. However, the correct institutional affiliation at the time of publication should have been: (d) Convergence Research Center for Solutions to Electromagnetic Interference in Future-mobility, Korea Institute of Science and Technology, 5 Hwarang-ro 14-gil, Seongbuk-gu, Seoul 02792, Republic of Korea. This corrigendum is issued to accurately reflect Dr. Park's institutional affiliation and to ensure that the scientific record properly documents his contribution. We sincerely appreciate the editor's and publisher's consideration in allowing this correction, as this information is essential for the accurate reporting of national R&D project outcomes and institutional acknowledgment. The authors regret the error and the oversight that led to this incorrect attribution. The authors would like to apologize for any inconvenience caused.